2022
DOI: 10.1136/bmjopen-2021-058377
|View full text |Cite
|
Sign up to set email alerts
|

Model of delivery of cancer care in South Africa’s Eastern Cape and Mpumalanga provinces: a situational analysis protocol

Abstract: IntroductionCancer contributes to a significant proportion of morbidity and mortality globally. Low-income and middle-income countries such as South Africa tend to be characterised by poor and inequitable access to cancer services. Cancer resources are more likely to be found in urban areas, tertiary centres and quaternary hospitals. However, little is known about the linkages to care, continuity of care and packages of cancer care in rural South African settings. This study describes cancer service delivery f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This study finds a higher number of beneficiaries diagnosed with breast cancer, nearly ten times more than those diagnosed with cervix cancer. These findings are consistent with the literature, where breast cancer is the most common cancer in women [20][21][22]27]. The study also found that 97% of breast cancer was diagnosed in females than in males, who accounted for 3 % of breast cancer, slightly higher than another study conducted in the public sector the study found the rate of 1.4% [33].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study finds a higher number of beneficiaries diagnosed with breast cancer, nearly ten times more than those diagnosed with cervix cancer. These findings are consistent with the literature, where breast cancer is the most common cancer in women [20][21][22]27]. The study also found that 97% of breast cancer was diagnosed in females than in males, who accounted for 3 % of breast cancer, slightly higher than another study conducted in the public sector the study found the rate of 1.4% [33].…”
Section: Discussionsupporting
confidence: 92%
“…Breast cancer is the most common cancer among women and the top cause of death in more than 100 countries worldwide [20][21][22]. Over two million new breast cancer cases have been detected worldwide, representing a quarter of all cancer cases in women [20,23,24].…”
Section: Breast Cancermentioning
confidence: 99%
See 3 more Smart Citations